Learning Management System (LMS) Application Design Using The Laravel Framework: Case Study: SMKS Bina Essa - Deni Sopiyan (LPPM STMIK Mardira Indonesia, 2025)
The advancement of information technology has profoundly influenced the education sector, especially in facilitating effective and efficient online learning methodologies. SMKS Bina Essa, as a vocational education institution, necessitates a system that enables teaching and learning activities to be conducted in a digital, integrated, and readily accessible manner for both educators and learners. This study seeks to develop a web-based Learning Management System (LMS) using the Laravel framework to improve learning management at SMKS Bina Essa. The applied system development methodology is Object-Oriented Analysis and Design (OOAD), encompassing steps such as needs analysis, system modeling through use case diagrams, class diagrams, sequence diagrams, activity diagrams, and user interface design. This research culminates in the design of the LMS program, incorporating essential elements such as user management for administrators, educators, and learners; management of educational resources; assignment processing; online assessments; discussion forums; and grade summarization and reporting. According to the results of black-box testing, all application functions meet user requirements. This application enhances the learning process at SMKS Bina Essa by making it more structured, engaging, and conducive to sustainable digital learning practices, while also supporting the deployment of blended learning within the school environment.